Behaviors of Precast Concrete Beam-Column Joints Under Dynamic Loading - Jitmart, Phonlakit; Chusilp, Nuntachai; Laksanakit, Chuthamat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This paper presents the behavior of precast concrete beam-column joints under dynamic loading, Compares two types of beam-column joints: cast in place beam-column joints (CCJ) and precast beam-column joints with plate and tube (PCPT). The experimental setup consists of square columns (150 × 150 mm, height 450 mm) and rectangular beams (150 × 250 mm, length 500 mm on both sides of the column). The PCPT joints incorporate a rectangular steel tube (100 × 50 mm, 4.5 mm thickness, 300 mm length) at the joints. Static loading at the column’s midspan and dynamic loading at 40 % 60 % and 80 % of the static load, with frequencies of 1.0 - 5.0 Hz, were applied. The results reveal that the ultimate static load capacities of CCJ and PCPT were 225.90 kN and 193.04 kN, respectively. Under dynamic loading, cracking increased proportionally with load ratio and frequency. The PCPT joints demonstrated superior performance under 80 % load at a frequency of 5.0 Hz, sustaining 200 cycles. Finite element analysis calibrated against experimental results showed maximum static load capacities of 234.86 kN for CCJ and 205.90 kN for PCPT, with deviations of 3.96 % and 6.66 % from the experimental results, respectively. The test results indicate that reinforcing beam-column joints of precast concrete with steel tube can be developed to enhance the performance of the joints in resisting dynamic loads over extended periods under service loading, compared to cast in place beam-column joints.